Intravenous Versus Oral Antibiotics for the Prevention of Treatment Failure in Children With Complicated Appendicitis: Has the Abandonment of Peripherally Inserted Catheters Been Justified? - Rangel, Shawn J; Anderson, Brett R; Srivastava, Rajendu; Shah, Samir S; Ishimine, Paul; Srinivasan, Mythili; Bryan, Matthew; Gong, Wu; Hall, Matt; Localio, Russell; Luan, Xianqun; Anandalwar, Seema; et al. (Annals of surgery, 2017)
To compare treatment failure leading to hospital readmission in children with complicated appendicitis who received oral versus intravenous antibiotics after discharge. Antibiotics are often employed after discharge to prevent treatment failure in children with complicated appendicitis, although existing studies comparing intravenous and oral antibiotics for this purpose are limited. We identified all patients aged 3 to 18 years undergoing appendectomy for complicated appendicitis, who received postdischarge antibiotics at 35 childrens hospitals from 2009 to 2012. Discharge codes were used to identify study subjects from the Pediatric Health Information System database, and chart review confirmed eligibility, treatment assignment, and outcomes. Exposure status was based on outpatient antibiotic therapy, and analysis used optimal and full matching methods to adjust for demographic and clinical characteristics. Treatment failure (defined as an organ-space infection) requiring inpatient readmission was the primary outcome. Secondary outcomes included revisits from any cause to either the inpatient or emergency department setting. In all, 4579 patients were included (median: 99/hospital), and utilization of intravenous antibiotics after discharge ranged from 0% to 91.7% across hospitals. In the matched analysis, the rate of treatment failure was significantly higher for the intravenous group than the oral group [odds ratio (OR) 1.74, 95% confidence interval (CI) 1.05-2.88; risk difference: 4.0%, 95% CI 0.4-7.6%], as was the rate of all-cause revisits (OR 2.11, 95% CI 1.44-3.11; risk difference: 9.4%, 95% CI 4.7-14.2%). The rate of peripherally inserted central catheter line complications was 3.2% in the intravenous group, and drug reactions were rare in both groups (intravenous: 0.7%, oral: 0.5%). Compared with oral antibiotics, use of intravenous antibiotics after discharge in children with complicated appendicitis was associated with higher rates of both treatment failure and all-cause hospital revisits.